IMPLEMENTASI SISTEM PENJAMINAN MUTU PENDIDIKAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Risal Sammara; Hasbi Hasbi (Kelola: Journal of Islamic Education Management, 2023)
This study examines the Implementation of an Internal Quality Assurance System in Improving Educationional Quality at SDN 2 Pinceppute, Wara Barat District, Palopo City. This study aimed at describing 1) the implementation of Internal Quality Assurance at SDN 2 Pinceppute, Wara Barat District, Palopo City, 2) the Internal/external factors that contribute in improving the quality of education at SDN 2 Pinceppute, Wara Barat District, Palopo City, 3) the Cycle of Internal Quality Assurance System SDN 2 Pinceppute, Wara Barat District, Palopo City. This research is a qualitative research with a multi-disciplinary approach, namely pedagogical, psychological, and sociological. Data collection was carried out by interviews, observation, and documentation. Management of data using the form of descriptions obtained through observation, documentation, and interviews. The data analysis used were data reduction, data presentation and conclusion. The results obtained in this research are those an Internal Quality Assurance System at SDN 2 Pinceppute conducted by a team, called School Education Quality Assurance Team. In carring out its duty worked based on the instruction by Educational  Quality Assurance Agency of South Sulawesi. Internal factors that contribute in improving the quality of education at SDN 2 Pinceppute are superior human resources, adequate infrastructure, high school principal motivation, and good cooperation between all stakeholders at SDN 2 Pinceppute while external factors contribute in improving the quality of education at SDN 2 Pinceppute is the support from parents and related agencies, while the inhibiting factors for the implementation of education quality assurance at SDN 2 Pinceppute  is financing and the environment is not conducive. The internal quality assurance cycle consisting of mapping educational quality, planning quality compliance, implementing quality compliance, monitoring and evaluation and setting new standards.